Attitudes toward persons with epilepsy as friends: Results of a factorial survey - Walther, Katrin; Kriwy, Peter; Stritzelberger, Jenny; Graf, Wolfgang; Gollwitzer, Stefanie; Lang, Johannes; Reindl, Caroline; Schwab, Stefan; Welte, Tamara; Hamer, Hajo (Epilepsia, 2023)
Objective: Discrimination against persons with epilepsy (PWEs) may persist. The aim of this study was to examine whether epilepsy is an obstacle to desired friendship.Methods: A factorial survey (vignettes), which is less biased by social desirability, was applied to PWEs, their relatives, and lay persons. The vignettes described a person who was varied by the dimensions of age (younger, same age, older), gender (male, female), disease (healthy, mild epilepsy, severe epilepsy [generalized toni-clonic seizures], diabetes), origin (German, non-German), contact (phone/internet, activities at home, activities outside), frequency of contacts (weekly, monthly), and distance (around the corner, 10 km away). Respondents rated their willingness to befriend the person on a 10-point Likert scale. Multivariate regression determined the contribution of each dimension on the judgment.Results: Participants were 64 PWEs (age = 37.1 +/- 14.0 years), 64 relatives of PWEs (age = 45.1 +/- 13.6 years), and 98 controls without contact with PWEs (age = 24.4 +/- 10.1 years). Controls were less interested in a friendship with a PWE with mild epilepsy (-3.4%) and even more avoided PWEs with severe epilepsy (-11.7%), whereas in PWEs with toni-clonic seizures, a mild form of epilepsy was actually conducive to friendship (+7.0%). Controls preferred females (+5.0%) and disliked younger people (-12.3%) and contacts via the internet or telephone (-7.3%). PWEs were also less interested in younger people (-5.8%), and relatives of PWEs had a lower preference for friendships with longer distance (-2.3%).Significance: PWEs still suffer from a risk of social avoidance, and this becomes more evident with generalized motor seizures.
CRIS-Team WoS Importer:2023-02-03